Antibacterial and antifungal properties of the methanol extract from the stem of Argyreia argentea - Md. Atiar Rahman, Taslima Ahsan, Saiful Islam (Bangladesh Pharmacological Society, 2010)
Antibacterial properties of methanol extract of Argyreia argentea stem was studied on three Gram positive and seven Gram negative bacteria by disc diffusion method. The extract showed zone of inhibition against Gram positive bacteria (Bacillus cereus, B. subtilis and B. megaterium) and Gram negative bacteria (Streptococcus aureus, E. Coli, Salmonella typhae, S. paratyphae, Pseudomonous sp (I), Pseudomonous sp (II) and Shigella sonnei). In addition, the extract was found effective against some fungi like Aspergillus flavous, Fusarium equiseti, Altenaria alternate, A. niger, Colletotrichum corphori.